Acute Radiation-Induced Changes in Sprague-Dawley Rat Submandibular Glands: A Histomorphometric Analysis - Krishnan, Manu (World J Oncol, 2017)
BACKGROUND: Radiation-induced xerostomia is a distressing clinical condition that starts appearing from the initial stages of radiotherapy in head and neck cancer patients. Though submandibular glands contribute to maximum of the “resting salivary” secretions, most of the acute xerostomia experiments so far reported have been on animal parotid glands. Therefore, we assessed and quantified the histologic changes in submandibular glands of Sprague-Dawley (SD) rats using histomorphometry, 24 hours after radiation. METHODS: Three SD rats were given single-dose radiation of 15 Gray from a gamma cobalt-60 irradiator. Same number of non-radiated animals was the controls. Animals were sacrificed at 24 hours followed by histopathology and histomorphometry of submandibular glands, where the mean values were analyzed by Student’s t-test. RESULTS: Irradiated submandibular glands showed highly significant reduction in acinar area (53%: 77.16±5.05% to 36.55±4.90%) and acinar size (87%: 3,447.53 ± 461.03 mm(2) to 428.25 ± 75.22 mm(2)) with concomitant increase in inter-acinar space (3.46 ± 0.67 mm to 10.08 ± 0.60 mm). Acini nuclei displayed anisonucleosis, poikilonucleosis and pyknosis. “Serous acini” had marked morphologic changes, with fluid accumulation between cells, generalized cytoplasmic vacuolation and vascular congestion, while “mucous acini” largely retained cell architecture. Similarly, ductal cells and nuclei also did not show apparent differences. This demonstrated radiosensitivity variations among different submandibular gland cell types. CONCLUSION: Evaluation of acute submandibular acinar cell dysfunctions has helped in quantifying the histologic elements, which mainly contribute to the resting salivary secretions. Findings would aid in future research of radioprotector drugs, salivary glandular regeneration modalities and in devising prudent radiotherapy protocols to address radiation-induced xerostomia.